2016
DOI: 10.1016/j.micromeso.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and stable Ni/SBA-15 catalysts prepared by a “two solvents” method for dry reforming of methane

Abstract: Two series of Ni (2.5 to 7.5 wt%) and Ce (6 wt%) containing SBA-15 catalysts were prepared and tested in dry reforming of methane, a promising route for the production of syngas. Both Ni and Ce species were introduced in the organized mesoporous silica support in the form of nitrate salts using the "two solvents" procedure that is known to favor metal dispersion inside the porosity. Samples characterizations by N 2 sorption, SAXS, XRD, SEM and TEM indicate good preservation of the porosities after Ni depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 68 publications
2
56
0
Order By: Relevance
“…It resulted in better dispersion of small Ni nanoparticles with narrower size distributions compared to the respective one prepared by classical impregnation method without using chelating ligands (Figure 7) [82]. The prepared catalysts showed stable catalytic activity towards DRM at 750 • C for 40 h and the size of Ni particles inside pores of SBA-15 silica was confined by pore structures of parent supports [82]. Reprinted with permission from Ref.…”
Section: Enhancement Of Dispersion and Thermal Stability Of Ni Nanopamentioning
confidence: 98%
See 2 more Smart Citations
“…It resulted in better dispersion of small Ni nanoparticles with narrower size distributions compared to the respective one prepared by classical impregnation method without using chelating ligands (Figure 7) [82]. The prepared catalysts showed stable catalytic activity towards DRM at 750 • C for 40 h and the size of Ni particles inside pores of SBA-15 silica was confined by pore structures of parent supports [82]. Reprinted with permission from Ref.…”
Section: Enhancement Of Dispersion and Thermal Stability Of Ni Nanopamentioning
confidence: 98%
“…Kang et al used a polyethyleneimine (PEI) as a chelating ligand of Ni precursors during impregnation processes [82]. Ni-PET complexes were well distributed inside the pores and strongly bound the SBA-15 silica surface through the strong interaction between NH 2 terminal groups of PEI and surface silanol groups of silica.…”
Section: Enhancement Of Dispersion and Thermal Stability Of Ni Nanopamentioning
confidence: 99%
See 1 more Smart Citation
“…For SRM and DRM catalysts, it was recently found that confinement of the nickel active phase within structured pores of oxide supports, especially mesoporous silica [40][41][42] or alumina [43][44][45][46], helps minimizing Ni 0 sintering during reaction, thus preserving reactivity with time on stream.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that mesoporous SBA-15 silica support is promising for the confinement and stabilization of nickel in DRM reaction [10,11]. The addition of ceria to Ni/SBA-16 catalysts was studied by Zhang et al [12] and the results showed that NiCe/SBA-16 was more stable, exhibiting higher conversion than Ni/SBA-16 in DRM.…”
Section: Introductionmentioning
confidence: 99%